Smart Cities and Positive Energy Districts: Urban Perspectives in 2020 - Maestosi, Paola Clerici (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Since their creation eight years ago, the EERA Joint Programmes and their participating institutions have accumulated important knowledge on specific topics of the programmes they carried out. This includes Smart Cities and Positive Energy Districts, which are not only crucial topics tackled by EERA Joint Programme in the Smart Cities Workplan, but also in H2020 as well as Horizon Europe or national calls, focusing on innovative solutions based on interdisciplinary approaches, which are needed to face the highly complex challenges in coming years, from sustainable urban development to emergencies in cities due to the COVID-19 pandemic. The foreword of EERA JP in SC Special Issue 1|2018 highlighted the aim of the Special Issues series, which was, and still is, to support the growth of research networks in the EC framework. According to this, our ambition is to publish the most promising research and innovation projects which EERA JPonSC partners, and others, set up in the framework of H2020 Programme, to drive the attention to the fact that EERA JP on SC is one of the strong voices in research in Europe, capable of highlighting and integrating different solutions and points of view.